Experimental investigation of effect of specimen thickness on fracture toughness of Al-TiC composites - M. S. Raviraj; C. M. Sharanaprabhu; G. C. Mohankumar (Fracture and Structural Integrity)
In this paper, the macro and micro-mechanical fracture behavior was studied for aluminum (Al6061) alloy matrix, reinforced with various proportions of TiC particles such as 3wt%, 5wt% and 7wt%. The Al6061-TiC metal matrix composites were produced by stir casting method to ensure uniform distribution of the TiC particulates in the Al matrix. The compact tension (CT) specimens were machined according to ASTM E399 specifications to evaluate the fracture toughness for Al6061-TiC metal matrix composites. The CT specimens were machined for crack to width (a/W) ratio of 0.5 and thickness to width (B/W) ratios of 0.2 to 0.7 with an increment of 0.1. Load versus crack mouth opening displacement (CMOD) data was plotted to estimate stress intensity factor KQ for various thicknesses of the specimen. The fracture toughness KIC was obtained by plotting stress intensity factor versus thickness to width ratios of specimen data. The fracture toughness of these composites varied between 16.4-19.2 MPa√m. Scanning Electron Microscope (SEM) studies was made on the fractured surface of the specimens to understand the micro-mechanisms of failure involved in these composites. Void initiation is more significant in the matrix near the interface. The micro-cracks grow from these micro-voids and crack propagates by linking these micro cracks locating the crack path preferentially in the matrix adjacent to the interface indicating ductile fracture.